(untitled) (Indian Journal of Animal Production and Management, 2024)
The reproductive efficiency of dairy animals is having a direct impact on productivity and profitability of dairy farms. Therefore, reproduction management is a major concern in dairy industry. Communication of the timing of physiological event of ovulation and coordination of sexual behavior are important for successful fertilization. The success rate of artificial insemination in cattle mainly depends on the time of estrus it is inseminated. Inefficient and inaccurate heat detection results in failure of conception during that attempt, which in turn leads to significant economic losses. The efficient and accurate detection of estrus and the timing of AI has remained major challenge to improve reproductive and economic efficiencies of dairy farms. To have a simple and accurate technique for optimizing the time of insemination, present investigation was performed on healthy, cyclic Sahiwal cows which had calved recently and were maintained at DDD farm of LFC, DUVASU, Mathura with an aim to investigate the behaviour of the cows in order to discriminate the various stages of estrus. The behavioral attributes of teaser bull and experimental cows were observed during three different stages i.e. onset of estrus, standing heat and non-estrus stages of same cows. It was observed that frequency of mounting by teaser bulls, frequency of Flehmen reaction by teaser bulls, restlessness of Sahiwal cows, bellowing and frequency of urination were all significantly affected by different stages of estrus i.e onset of estrus, standing heat and non-estrus.